Multiple Interference Cancellation Performance for GPS Receivers with Dual-Polarized Antenna Arrays. (25th November 2008) - Wang Wang, Jing Jing; Amin Amin, Moeness G. Moeness G.
Abstract : This paper examines the interference cancellation performance in global positioning system (GPS) receivers equipped with dual-polarized antenna arrays. In dense jamming environment, different types of interferers can be mitigated by the dual-polarized antennas, either acting individually or in conjunction with other receiver antennas. We apply minimum variance distorntionless response (MVDR) method to a uniform circular dual-polarized antenna array. The MVDR beamformer is constructed for each satellite. Analysis of the eigenstructures of the covariance matrix and the corresponding weight vector polarization characteristics are provided. Depending on the number of jammers and jammer polarizations, the array chooses to expend its degrees of freedom to counter the jammer polarization or/and use phase coherence to form jammer spatial nulls. Results of interference cancellations demonstrate that applying multiple MVDR beamformers, each for one satellite, has a superior cancellation performance compared to using only one MVDR beamformer for all satellites in the field of view.